Characterization of chemical reactions of silver diammine fluoride and hydroxyapatite under remineralization conditions - Kaur, M.; Shahid, S.; Karpukhina, N.; Anderson, P.; Wong, F. S. L. (Frontiers in Oral Health, 2024)
Introduction Silver Diammine Fluoride (SDF) is a clinically used topical agent to arrest dental caries. However, the kinetics of its chemical interactions with hydroxyapatite (HA), the principal inorganic component of dental enamel, are not known. The aim was to characterize the step-wise chemical interactions between SDF and HA powder during the clinically important process of remineralization. Methods Two grams of HA powder were immersed in 10 ml acetic acid pH = 4.0 for 2 h to mimic carious demineralization. The powder was then washed and dried for 24 h and mixed with 1.5 ml SDF (Riva Star) for 1 min. The treated powder was then air-dried for 3 min, and 0.2 g was removed and stored in individual tubes each containing 10 ml remineralizing solution. Powder was taken from each tube at various times of exposure to remineralization solution (0 min, 10 min, 2 h, 4 h, 8 h, 24 h, and 10 days), and characterized using Magic Angle Spinning-Nuclear Magnetic Resonance (MAS-NMR) spectroscopy. Results and discussion 19F MAS-NMR spectra showed that calcium fluoride (CaF2) started to form almost immediately after HA was in contact with SDF. After 24 h, the peak shifted to −104.5 ppm suggesting that fluoride substituted hydroxyapatite (FSHA) was formed with time at the expense of CaF2. The 31P MAS-NMR spectra showed a single peak at 2.7 ppm at all time points showing that the only phosphate species present was crystalline apatite. The 35Cl MAS-NMR spectra showed formation of silver chloride (AgCl) at 24 h. It was observed that after the scan, the whitish HA powder changed to black color. In conclusion, this time sequence study showed that under remineralization conditions, SDF initially reacted with HA to form CaF2 which is then transformed to FSHA over time. In the presence of chloride, AgCl is formed which is subsequently photo-reduced to black metallic silver.